2023
DOI: 10.1021/acs.macromol.2c02286
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Block-Random Copolymers: Shedding Light on Aqueous Self-Assembly Behavior

Abstract: The aqueous solution and aggregation behavior of polystyrene-b-poly­[styrene-r-(acrylic acid)] block-random copolymers have been examined. Previous work conducted by our group showed that these materials exhibit an unanticipated ease of dispersion in water compared to polystyrene-b-poly­(acrylic acid) block copolymers of similar molecular weight and composition. Herein, fluorescence labeling experiments and the presence of a critical aggregation concentration suggest the self-assembly of these materials into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…24 The block–random copolymers exhibit unusual behaviour when dispersed in alkaline media, where it was suspected they self-assemble into low aggregation number aggregates. 25 A preliminary study showed that a 200 nm diameter latex of polystyrene with a proportion of 5–10 w/v% based on monomer volume (BoM) could be efficiently polymerised. While classic surfactants and block copolymers exhibit a particle number dependence on the stabiliser concentration ( N p ∝ [S] α ) closer to square root or linear ( α = 0.6–1.0), polymerisations stabilised using BRCs exhibit a cubic relationship ( α = 3), specific and unique to this new class of copolymer when used in emulsion polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…24 The block–random copolymers exhibit unusual behaviour when dispersed in alkaline media, where it was suspected they self-assemble into low aggregation number aggregates. 25 A preliminary study showed that a 200 nm diameter latex of polystyrene with a proportion of 5–10 w/v% based on monomer volume (BoM) could be efficiently polymerised. While classic surfactants and block copolymers exhibit a particle number dependence on the stabiliser concentration ( N p ∝ [S] α ) closer to square root or linear ( α = 0.6–1.0), polymerisations stabilised using BRCs exhibit a cubic relationship ( α = 3), specific and unique to this new class of copolymer when used in emulsion polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publications, we believed the BRCs formed either single-chain nanoparticles or low N agg aggregates, which contributed to the unique nucleation mechanism in emulsion polymerizations of styrene stabilized by BRCs. , It is now established that self-assembly of BRC chains into multichain aggregates occurs rather than a self-folding process at pH > 9.5 and Φ ∼ 100 mM . Moreover, Förster resonance energy transfer (FRET) experiments showed that the unimer exchange between aggregates over 6 h was not detectable at room temperature and became significant at elevated temperatures (90 °C).…”
Section: Resultsmentioning
confidence: 99%
“…26 Recently, our group has been studying PS-b-P(S-r-AA) block−random copolymers (BRC) as stabilizers in emulsion polymerization 27−29 and in solution. 30 Typical compositions of the BRC are approximately 60−85 mol % styrene and 15−40 mol % acrylic acid. Block copolymers of PS-b-PAA with >50 mol % acrylic acid are often applied in emulsion polymerizations to ensure ease of copolymer dispersion in aqueous conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations